SISTEM INFORMASI PENGGAJIAN PEGAWAI Di SMK MUHAMADIYAH 3 WATES - Riyanto, Ari Budi (Universitas Perwira Purbalingga, 2021)
The purpose of this study is to build an information system related to computerbased systems, so that the process can be done more quickly and efficiently and can be something that can happen. The research method is done by completion of literature data, interview (interview), direct observation (observation whilst the development of information system method which was used is System Development Life Cycle (SDLC) the steps are; system analysed, system design, system implementation, operation and preservation. From the observations and research conducted, it can be seen that SMK Muhammadiyah 3 Wates requires effective and efficient processing of payroll information, and other information, so that it is expected to produce better information with a computerized system.